Επιρροή των συνθηκών στήριξης στην Ανάλυση Τρωτότητας πολυώροφου κτιρίου - Κυνηγός, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Πολιτικών Μηχανικών, 2017)
The purpose of this study, is to investigate the effect of the conditions assigned to the base of the structure during the modeling process and thus to evaluate one aspect of the soil – structure interaction phenomenon. For this purpose, a four – storey braced frame steel structure is designed according to the modern provisions of Eurocodes (Ec-3, Ec-8). A modal analysis is implemented which is needed for the spectral modal analysis of the seismic load design. The following analysis steps are afterwards defined.